1990
DOI: 10.1037/0022-3514.59.5.960
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the accuracy of self-evaluations of performance.

Abstract: Research has shown that gender differences in self-perceptions exist. However, interpretational ambiguities make it impossible to determine whether these gender differences are due to the operation of biases. The present research investigated whether gender differences in biased selfperceptions exist by assessing the accuracy of posttask self-evaluations of performance. In accordance with self-consistency theory, it was hypothesized that Ss' expectancies affect their posttask self-evaluations. For example, men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
277
2
13

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 456 publications
(313 citation statements)
references
References 79 publications
21
277
2
13
Order By: Relevance
“…This may imply that only women downgrade their self-assessment in Info due to a stronger (anticipated) social disapproval of their overconfidence. 6 Regardless of the root cause for the shame to overestimate oneself, we find that women are more shame-averse than men. Women's shame-aversion may lead to more cautious behavior and self-promotion?…”
Section: Introductionmentioning
confidence: 70%
“…This may imply that only women downgrade their self-assessment in Info due to a stronger (anticipated) social disapproval of their overconfidence. 6 Regardless of the root cause for the shame to overestimate oneself, we find that women are more shame-averse than men. Women's shame-aversion may lead to more cautious behavior and self-promotion?…”
Section: Introductionmentioning
confidence: 70%
“…While many studies have focused on self-assessment of IQ or other intelligence measures (Beyer and Bowden 1997, Beyer 1990, Furnham 2001, Furnham et al 2002, similar effects have been observed in work performance reviews and many other domains (Beyer 1990, Beyer et al 2003, Blanch et al 2008. This difference seems to stem, in part, from social pressure for female modesty (Furnham et al 2002), coupled with a lower self-attribution bias among women, in that they are less likely to falsely attribute their success to their own efforts (Beyer 1990, Miller andRoss 1975).…”
Section: Persistence and The Founding Gapmentioning
confidence: 84%
“…The "male hubris, female humility" effect has been repeatedly identified in many studies and contexts: men consistently overestimate their own abilities while women consistently underestimate theirs (Beyer and Bowden 1997, Beyer 1990, 1998, Cross and Madson 1997, Furnham et al 2002. These findings have been shown to be "universal" across multiple cultures (Furnham et al 2002).…”
Section: Persistence and The Founding Gapmentioning
confidence: 92%
See 2 more Smart Citations